FORMATION OF LAND RENT IN KHERSON PROVINCE IN THE CONDITIONS OF CAPITALIST SHIFTS - Чернікова, Наталія (SWorldJournal, 2025)
The article considers the process of institutionalization of lease relations in the agricultural sector of the Kherson province in the second half of the XIX cent.- 1917 in the conditions of development of commodity agriculture and animal husbandry. The